MANAJEMEN PENDIDIKAN KARAKTER SEKOLAH ISLAM TERPADU BERBASIS PESANTREN - Nizarani Nizarani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research aimed to know how the management of character education in Integrated Islamic Boarding School. This research used qualitative approach, the techniques of the data collection are by conducting interview, observation, and documentation. The data is obtained from the principal of Students’ Affairs, Teachers, and the chief of students Association of Raudhatul Ulum.The data analyzed by using content analysis technique. Based on the research result, it can be concluded that 1) The planning of character education in SMA IT Raudhatul Ulum through the meetings of school administrators and teachers who discuss formal and informal daily, mounthly and annual school program based on the National Education Curriculum, JSIT curriculum, and Islamic Boarding Curriculum; 2) Organizing character education is carried out by school under the primary responsibility of vice principal of curriculum and students affairs; 3) The form of implementation is by developing a curriculum consisting of integration in learning school programs, habituation and example; 4) Controlling is carried out by all elements in the school, both daily, weekly, monthly and annual activities. The form of evaluation is through the meeting of all teachers ang school administrators, monthly report of school administrator and report book.